2012
DOI: 10.1089/mdr.2011.0063
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in therrsA1401G Gene and Phenotypic Resistance to Amikacin and Capreomycin inMycobacterium tuberculosis

Abstract: The aminoglycosides amikacin (AMK)/kanamycin (KAN) and the cyclic polypeptide capreomycin (CAP) are important injectable drugs in the treatment of multidrug-resistant tuberculosis. Cross-resistance among these drug classes occurs and information on the minimum inhibitory concentrations (MICs), above the normal wild-type distribution, may be useful in identifying isolates that are still accessible to drug treatment. Isolates from the Eastern Cape Province of South Africa were subjected to DNA sequencing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 22 publications
1
50
1
Order By: Relevance
“…These results suggest that the MGIT or MycoTB method should be preferred for testing phenotypic resistance to KAN. They also highlight the power of genotypic resistance tests, such as ours, to detect mutations which cause low-level resistance and may be missed by phenotypic tests alone (30,31,36).…”
Section: Discussionmentioning
confidence: 83%
“…These results suggest that the MGIT or MycoTB method should be preferred for testing phenotypic resistance to KAN. They also highlight the power of genotypic resistance tests, such as ours, to detect mutations which cause low-level resistance and may be missed by phenotypic tests alone (30,31,36).…”
Section: Discussionmentioning
confidence: 83%
“…It is therefore possible that the WHOrecommended critical concentration that we used here resulted in the misclassification of CAP-resistant organisms as "susceptible" when, in fact, they contained the 1401 A-G mutation in the rrs, ultimately resulting in the reduced specificity of PSQ for predicting phenotypic CAP resistance. In addition, as discussed in Sirgel et al (40), clinical isolates from South Africa with the 1401 A-G mutation in the rrs gene showed decreased phenotypic susceptibility to CAP. Furthermore, while the rrs 1401 A-G mutation is implicated in cross-resistance to all three injectable drugs, some studies have shown that mutations outside our considered genomic regions, most notably mutations in eis promoter and tlyA, may independently confer resistance to KAN and CAP, respectively (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 84%
“…Finally, no mutation in tlyA was observed in any of our isolates, so tlyA does not seem to be implicated in CAP resistance in our MDR clinical isolates. Mutations in the tlyA gene associated with CAP resistance were reported to be rare in the surveyed literature (found in ϳ0 to 3% of resistant strains), and their implication in resistance has not been undoubtedly established (4,7,8,10,11,14,(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%